Metabotropic Glutamate Receptor Signalling and Phenotype Progression in Huntington's Disease Mice - Li, Si Han (Université d'Ottawa / University of Ottawa, 2023)
Huntington's disease (HD) is an inherited autosomal-dominant neurodegenerative disease caused by the abnormal expansion of CAG repeats in exon 1 of the huntingtin gene located on chromosome 4. This disease is characterized by the premature loss of medium spiny neurons in the striatum and behavioural deficits that typically manifest at middle-age. Despite the identification of its cause decades ago, there is still no disease modifying treatment available for HD patients. Current evidence indicates that exacerbated glutamate signalling in the striatum plays a key role in the pathophysiology of HD. Within the striatum, metabotropic glutamate receptor (mGluR) 2/3 are predominantly expressed on presynaptic terminals, whereas mGluR5 is predominantly localized to postsynaptic terminals. Here, we show that both the activation of mGluR2/3 and the inhibition of mGluR5 can improve HD symptoms in the zQ175 HD mouse model. Specifically, treating zQ175 HD mice with either the mGluR2/3 agonist LY379268 or the mGluR5 negative allosteric modulator (NAM) CTEP rescues motor deficits, reduces mutant huntingtin aggregate formation, improves neuronal survival and alleviates microglia activation. We also provide evidence that shows sex can influence the progression of HD symptoms and the efficacy of therapeutic agents. We found that chronic administration of LY379268 differentially activated and inactivated cell signalling pathways in male and female zQ175 mice. Furthermore, female zQ175 mice required a longer treatment duration with CTEP than male mice to show improvement in their rotarod performance. Using FDNQ175 mice, a newer HD mouse model derived from the zQ175 line, we demonstrated that female FDNQ175 mice were less susceptible to decline in limb function than male mice but showed higher levels of insoluble mutant huntingtin aggregates at a younger age.
Keywords: Huntington's disease; Neurodegeneration; Metabotropic Glutamate Receptors